Hubungan Kepuasan Siswa Terhadap Sarana Prasarana Olahraga dengan Minat Belajar Siswa dalam Mata Pelajaran PJOK di Sman 1 Driyorejo - Ainun Jariyah; Shiva Aulia Ramadhani; Muhammad Surya Afrizal Nurdin; Diah Rahmawati; Rahma Ayu Wulandari; Ayu Wulandari (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2024)
This study aims to understand the relationship between students' satisfaction with sports facilities and their learning interest in PJOK subject at SMAN 1 Driyorejo. Adequate sports infrastructure is one of the important factors in supporting an effective learning process, students' satisfaction with sports infrastructure can affect their learning interest in actively participating during learning activities. The method in this research is using quantitative methods with data collection through questionnaires distributed to students of class XII 6 and XII 7 SMAN 1 Driyorejo. Based on data analysis obtained from the results of the spearman correlation test, which amounted to 0.729. Therefore, the data shows a very strong relationship. This means that the higher the level of student satisfaction with sports facilities, the greater their interest in participating in PJOK subjects.. The results of this study indicate that the relationship between sports infrastructure facilities and interest in learning PJOK at SMAN 1 Driyorejo is very high.